Group Exhibition-Vallasdaden 2017, Linkoping, Sweden - Antoniou, Klitsa (My University, 2026)
Vallasdaden 2017, Linkoping, Sweden. Organized by Norrkoping Air, Affiliated with Linkoping university, Curated by Costa Economou